2008
DOI: 10.1007/s11595-007-6917-x
|View full text |Cite
|
Sign up to set email alerts
|

Healing effectiveness of cracks rehabilitation in reinforced concrete using electrodeposition method

Abstract: An electrodeposition method and its experimental device for rehabilitation of cracks in reinforced concrete were proposed. Porous concrete is proposed to simulate cracked concrete, and mass increment, permeation coefficient and sound velocity of ultrasonic wave were used to be evaluating indicators of healing effectiveness of crack rehabilitation in this method. Effect of currency density, concentration of electrolyte solution on healing effectiveness of porous reinforced concretes with different total void ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…However, many experimental investigations have shown that there is interfacial transition zone (ITZ) between the deposition product and intrinsic concrete. Figure 1 shows the microstructures of ITZ according to Jiang et al (2004). The ITZ properties are influenced by many factors, such as the solution type and the current density (Chen, 2014;Chu and Jiang, 2009;Jiang et al, 2008;Otsuki and Ryu, 2001;Ryu, 2003b), which means that the perfect bonding assumption in our previous work is not reasonable all the time.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, many experimental investigations have shown that there is interfacial transition zone (ITZ) between the deposition product and intrinsic concrete. Figure 1 shows the microstructures of ITZ according to Jiang et al (2004). The ITZ properties are influenced by many factors, such as the solution type and the current density (Chen, 2014;Chu and Jiang, 2009;Jiang et al, 2008;Otsuki and Ryu, 2001;Ryu, 2003b), which means that the perfect bonding assumption in our previous work is not reasonable all the time.…”
Section: Introductionmentioning
confidence: 95%
“…As a promising repairing approach for damaged concrete in aqueous environment, the electrochemical deposition method (EDM) has been applied to marine structures and other situations in which traditional repairing methods are limited (Jiang et al, 2015;Yokoda and Fukute, 1992). Over the past 20 years, many literatures have been published on EDM, which mainly focus on the experimental research, including regarding specimen production (Chang et al, 2009;Ryu, 2003a;Ryu and Otsuki, 2005), factors influencing the healing effectiveness of EDM (Chu and Jiang, 2009;Otsuki and Ryu, 2001;Ryu, 2003b) and assessments of the healing effectiveness of EDM (Chen, 2014;Jiang et al, 2008;Otsuki et al, 1999;Ryu and Otsuki, 2002). However, there are few theoretical models pertaining to mechanical properties during the damage-healing process.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, numerous experimental studies have been conducted on the electrochemical deposition method (EDM), which is a promising approach to repair the concrete cracks under an aqueous environment (Chen, 2014; Jiang et al., 2008; Ryu, 2003a; Ryu, 2003b; Ryu and Otsuki, 2002; Ryu and Otsuki, 2005). However, few studies have disclosed the healing mechanism of the EDM with the rigorous analytical models.…”
Section: Introductionmentioning
confidence: 99%
“…Most concrete structures repaired using the EDM are not fully saturated in reality (Chatterji, 2004; Persson, 1997). Meanwhile, the interface between the deposition products and the concrete is not always perfect bonding (Chen, 2014; Jiang et al., 2008). To incorporate these two phenomena, micromechanical framework is presented for unsaturated concrete repaired by EDM with the bonding effects based on our latest work (Chen et al., 2015a; Zhu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, many meaningful studies have been published on the electrochemical deposition method (EDM), which is a promising repairing approach for concrete in aqueous environment and has been applied to marine structures and other situations in which traditional repairing methods are limited [1][2][3][4]. The current literatures mainly focus on the experimental research, including specimen production [5][6][7], factors influencing the healing effectiveness of EDM [8][9][10], and assessments of the healing effectiveness of EDM [11][12][13][14]. However, there are few theoretical models pertaining to mechanical properties during the EDM healing process.…”
Section: Introductionmentioning
confidence: 99%